2019
DOI: 10.1111/1744-9987.12781
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Transforming Growth Factor Beta‐1 Promotes Smooth Muscle Cell Proliferation and Migration in an Arteriovenous Fistulae: The Role of Wall Shear Stress

Abstract: The wall shear stress (WSS) as a mechanical stimuli to venous wall has a significant role in neointimal hyperplasia of arteriovenous fistulae (AVF), which is often related to the proliferation and migration of vascular smooth muscle cells (VSMCs). Transforming growth factor beta-1 (TGF-β1) has the function of promoting VSMCs proliferation and migration. Our study is to detect the correlation between WSS, TGF-β1, VSMCs proliferation, and neointimal hyperplasia. An "end-to-side" AVF canine model was created. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A further, focussed analysis of the signal transduction pathways revealed that 41 signalling pathways were affected by the reduction in shear stress. These included well-known shear stress-sensitive pathways such as eNOS and MAPK (Wang et al 2014;Riquelme et al 2015;Lee et al 2017;Kunnen et al 2018), recently established mechanosensitive pathways such as NOTCH and WnT (Kuo et al 2015;Kuo et al 2015;Jia et al 2018;Kunnen et al 2018;Xu et al 2018;Yang et al 2018;Bondareva et al 2019;Gater et al 2019;Han et al 2019;Kouzbari et al 2019;Varshney et al 2019;Yue et al 2019) and currently unknown mechanosensitive pathways like insulin (Table 2).…”
Section: A Central Role For Clusters In Mechanosensitive Pathway Coor...mentioning
confidence: 99%
“…A further, focussed analysis of the signal transduction pathways revealed that 41 signalling pathways were affected by the reduction in shear stress. These included well-known shear stress-sensitive pathways such as eNOS and MAPK (Wang et al 2014;Riquelme et al 2015;Lee et al 2017;Kunnen et al 2018), recently established mechanosensitive pathways such as NOTCH and WnT (Kuo et al 2015;Kuo et al 2015;Jia et al 2018;Kunnen et al 2018;Xu et al 2018;Yang et al 2018;Bondareva et al 2019;Gater et al 2019;Han et al 2019;Kouzbari et al 2019;Varshney et al 2019;Yue et al 2019) and currently unknown mechanosensitive pathways like insulin (Table 2).…”
Section: A Central Role For Clusters In Mechanosensitive Pathway Coor...mentioning
confidence: 99%